How future work self-salience influences occupational sense of mission among medical students in the post-pandemic era: a dual-perspective analysis from variable-centered and person-centered approaches based on professional identity - Zhong, Qihe; Zhou, Yiwen; Li, Junxian; Huang, Yingping (Frontiers in Public Health, 2026)
BackgroundIn the post-pandemic era, medical students face increased occupational uncertainty. Future work self-salience as a prospective dimension of self-awareness, shapes career choices and constitutes a core driver of professional engagement. However, few studies have explored the relationship between future work self-salience and occupational sense of mission among medical students or its underlying mechanisms. This study examines the associations among professional identity, future work self-salience, and occupational sense of mission in medical students in the post-pandemic era, as well as heterogeneity in these constructs.MethodsUsing a cross-sectional design and random sampling, 568 medical students were recruited from three comprehensive universities in Sichuan Province, China. Validated instruments measured future work self-salience, occupational sense of mission, and professional identity. A variable-centered approach (PROCESS Model 4) tested the mediating role of professional identity. A person-centered approach employed latent profile analysis to identify subtypes based on future work self-salience and professional identity, with one-way ANOVA examining differences in occupational sense of mission across profiles.ResultsVariable-centered analyses showed that future work self-salience positively predicted occupational sense of mission, with professional identity partially mediating this relationship. Person-centered analyses identified three distinct profiles: (1) High Future Work Self-salience–High Professional Identity, (2) Moderate Future Work Self-salience–Moderate Professional Identity, and (3) Low Future Work Self-salience–Low Professional Identity. ANOVA revealed that the High Future Work Self-salience–High Professional Identity profile exhibited the highest occupational sense of mission.ConclusionIn the post-pandemic era, medical students’ future work self-salience enhances their occupational sense of mission by strengthening professional identity; however, individual heterogeneity leads to differential effect magnitudes. Educational interventions targeting students with low occupational sense of mission should strengthen future work self-salience and professional identity training to elevate overall occupational sense of mission and support sustainable development of healthcare professionals in the post-pandemic context.